The Impact of Impending Credit Rating Changes on Management Earnings Forecasts (Global Journal of Management and Business Research, 2018)
This study investigates whether impending credit rating changes affect managers' voluntary financial disclosure behaviors. I find that firms near a credit rating change do not opportunistically alter their financial disclosure practices to manipulate rating agencies' perceptions about corporate credit risk. In particular, firms close to a credit rating change do not selectively release good news or withhold bad news in their earnings forecasts. Nor do the firms likely issue an optimistically biased forecast or a more precise forecast for good news than for bad news. Overall, there is no evidence suggesting that credit ratings are manipulated via management earnings forecasts.
Keywords: credit ratings; management earnings forecasts; forecast news; forecast accuracy; forecast precision